Mixed Methods Research in Criminology and Criminal Justice: a Systematic Review - Wilkes, Nicole (American journal of criminal justice, 2022)
The field of criminology and criminal justice encompass broad and complex multidisciplinary topics. Most of the research that falls under these areas uses either quantitative or qualitative methodologies, with historically limited use of mixed methods designs. Research utilizing mixed methods has increased within the social sciences in recent years, including a steadily growing body of mixed method research in criminal justice and criminology. The goal of this study was to examine how mixed method designs are being employed within research related to criminal justice and criminology. Our systematic review located 327 mixed method articles published between 2001 and 2017. Findings indicated most criminology and criminal justice research is being conducted within the specialty area of victimology. This study provides an overview of mixed methods research in criminology and criminal justice and also illustrates that most publications are not including methodological concepts specific to mixed methods research (e.g., integration). Along with our systematic review, we offer a series of recommendations to move mixed methods research forward in criminology and criminal justice.